Latin America and the Caribbean : atlas of our changing environment (UNEP and the Water Center for the Humid Tropics of Latin America and the Caribbean (CATHALAC) Panama CityPA, 2010)
Presents through cases, images, maps, tables, graphs and text - a picture of the ecosystems in Latin America and the Caribbean in the past the current situation. Tells the tale of how deforestation has contributed to the loss of biodiversity, of how those changes have likewise led to air and water pollution, degradation of the soil, the habitat, depletion of species due to overhunting, the introduction of invasive species, and the host of challenges peoples of this area face.
Keywords: ATLASES